Stress-Strength Interference Model for the Optimization of Test Coupon Engineering for Microvia Reliability - Syed Mujahid Abbas; Wahaj Abbas Awan; Muhammad Imran Haider; Heba G. Mohamed (IEEE Open Journal of Power Electronics, 2025)
The demand in the automobile electronic industry for compact printed circuit boards requires highly reliable microvias that work as an interconnect among the conducting layers of printed circuit boards. To meet industry needs, researchers have developed different testing coupons to capture the early failure of microvias using accelerated testing. However, the percentage of failing microvias is insignificant when considering the failure phenomenon. It highlights the need for a statistical model that can give a significant likelihood of failure microvias that can be reviewed for reliability studies. In this paper, we have developed a statistical test model of microvia using the stress-strength interference method to enhance the possibility of microvia failure to investigate the phenomenon of failure during thermomechanical loading. Finite element models were developed using the design of the experiment technique using the Taguchi method. The results showed a 12% increase in the probability of microvia failure, providing sufficient room to find the behavior of microvias that fail. Moreover, the simulation modeling results correlate with the literature models to verify the accuracy of the model.